Determinants of the increase in ketone concentration during SGLT2 inhibition in NGT, IFG and T2DM patients. Issue 6 (27th March 2017) - Al Jobori, Hussein; Daniele, Giuseppe; Adams, John; Cersosimo, Eugenio; Triplitt, Curtis; DeFronzo, Ralph A.; Abdul‐Ghani, Muhammad
Abstract : Aim: To examine metabolic factors that influence ketone production after sodium‐glucose cotransport inhibitor (SGLT2) administration. Research design and methods: Fasting plasma glucose (FPG), insulin, glucagon, free fatty acid and ketone concentrations were measured in 15 type 2 diabetes mellitus (T2DM) and 16 non‐diabetic subjects before and at day 1 and day 14 after treatment with empagliflozin. Results: Empagliflozin caused a 38 mg/dL reduction in FPG concentration in T2DM patients. However, it caused only a small but significant (7 mg/dL) reduction in the FPG concentration in impaired fasting glucose (IFG) subjects and did not affect FPG concentration in normal glucose tolerant (NGT) subjects. Empagliflozin caused a significant increase in mean plasma glucagon, free fatty acid (FFA) and ketone concentrations in T2DM subjects. However, empagliflozin did not cause a significant change in mean plasma insulin, glucagon or ketone concentrations in non‐diabetic subjects. An index that integrates change in plasma glucose, insulin and FFA concentration at day 1 strongly correlates with plasma ketone concentration at day 1 (r = 0.85, P < .001) and day 14 (r = 0.63, r = 0.01) and predicts, with 86% sensitivity and 83% specificity, subjects at the top tertile for plasma ketone concentration after empagliflozin treatment. Conclusion: Results of the present study demonstrate that SGLT2 inhibition exerts different metabolic effects in non‐diabetic individuals as compared to diabetic patients.